Now You Do It, Now You Don’t: The Mixed Blessing of Creative Deviance as a Prosocial Behavior - Shukla, Jigyashu; Kark, Ronit (Frontiers in Psychology, 2020)
Creative deviance, the act of developing an idea by an employee even when it was banned by the manager, is a novel and interesting construct that can bring both positive and negative outcomes to organizations. The construct of creative deviance is neglected in the existing literature and the theory development for creative deviance is still in the nascent stages. We expand the theoretical nomological network of creative deviance by introducing prosocial motivation as an antecedent of creative deviance and developing a multilevel model of the moderators of this relationship. Creative deviance can occur due to pro-self or prosocial intentions. In our paper, we focus on the prosocial intentions behind acts of creative deviance. We illustrate how prosocial motivation can lead to creative deviance and how creative deviance, in turn, can act as a double-edged sword leading to positive outcomes of creative performance and innovation as well as negative outcomes of wastage of resources and deteriorated leader-member exchange. Our model delineates the boundary conditions influencing the relationship between creative deviance and its outcomes. Specifically, we explore the theoretical foundations of social skills and perspective-taking, as the individual level moderators; team network structure and climate of excellence, as moderators at team level; organizational structure at organization level; and uncertainty as the external environmental level moderator.